2019
DOI: 10.1007/978-3-030-12092-4_5
|View full text |Cite
|
Sign up to set email alerts
|

Latvian Migrants in Foreign Labour Markets: Job Placement and Discrimination

Abstract: The majority of migrants from Latvia move abroad intending to work, and so fall into the category of ‘work migrants’. A crucial role in their job placement is played by an increasingly complex network of intermediaries. This includes formal employment agencies, more informal, social network-based mediators and even illegal service providers. Despite the agencies providing job placements abroad being subject to regulations, fraud and the mistreatment of jobseekers has emerged as a cause for concern. Even when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…At the same time, the findings of this study are in line with previous findings (Mierin , a 2016) that Latvian emigrants evaluate the attitude of employers abroad as being better than that of employers in Latvia, where they face unfair treatment even more often. However, in his study, Tabuns (2019) does not touch upon the relationship between migrants' perceived discrimination and their integration in the host country and other factors.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…At the same time, the findings of this study are in line with previous findings (Mierin , a 2016) that Latvian emigrants evaluate the attitude of employers abroad as being better than that of employers in Latvia, where they face unfair treatment even more often. However, in his study, Tabuns (2019) does not touch upon the relationship between migrants' perceived discrimination and their integration in the host country and other factors.…”
Section: Introductionmentioning
confidence: 93%
“…A sending-country perspective on perceived discrimination has been neglected and is under-researched. One of the few studies on discrimination against Latvian migrant workers abroad (Tabuns 2019) indicates that 35% of Latvian migrant workers have encountered some form of discrimination or unfair treatment in their workplace. The most common form of unfair treatment is an unfair salary: 18% have reported that they have been paid less than workers from the host nation for similar work.…”
Section: Introductionmentioning
confidence: 99%
“…The polarisation of Latvian speakers' and Russian speakers' views on domestic and geopolitical issues has been a problem throughout recent decades. Tabuns (2006: 32) noted that Latvia's Russian speakers who identify with Russia and the divergent geopolitical attitudes curtail successful political integration. These perceptions are rooted in different historical memories, spilling over into the perceptions of current events and manifesting during days of celebrations, where the Russian speakers mostly espouse different affinities from the rest (Baltic Institute of Social Sciences, 2015: 49; Ločmele et al, 2011).…”
Section: Introductionmentioning
confidence: 99%